MODERASI BERAGAMA: PERAN DAN TANTANGAN DALAM PEMBELAJARAN DI SEKOLAH DI ERA DIGITAL - Subiantoro, Subiantoro (LPPM Institut Pendidikan Nusantara Global, 2023)
Religious moderation is defined as an attitude aimed at reducing violence or avoiding extremism in religious practices to balance religious teachings. This is reflected in defending religious teachings while accepting opposing views. Religious moderation aims to bring harmony into the lives of others. The role of religious mediation that students must understand in the current digital era is as follows: 1) Peaceful education that respects human rights and friendship between nations, races or groups, 2) developing entrepreneurship and partnerships with industry, 3) paying attention to prophetic Islam, 4 ) include lessons about tolerance and religious pluralism, 5) understanding of Islam for it was passed down to a moderate anti-mainstream Indonesian Islamist, 6) balancing views between intellectual, spiritual, moral and casual abilities, 7) producing intellectual scholars, 8) solutions to educational problems , 9) emphasizing the holistic quality of education and 10) the ability to improve foreign language skills. In order to develop moderate students, there are many challenges to be faced, especially in the increasingly advanced digital era, such as the current decline in attachment to religious institutions, changes in religious theory and the strengthening of individualism.